2020
DOI: 10.1038/s41467-020-19177-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic elucidation of neuron-astrocyte interaction in models of amyotrophic lateral sclerosis using multi-modal integrated bioinformatics workflow

Abstract: Cell-to-cell communications are critical determinants of pathophysiological phenotypes, but methodologies for their systematic elucidation are lacking. Herein, we propose an approach for the Systematic Elucidation and Assessment of Regulatory Cell-to-cell Interaction Networks (SEARCHIN) to identify ligand-mediated interactions between distinct cellular compartments. To test this approach, we selected a model of amyotrophic lateral sclerosis (ALS), in which astrocytes expressing mutant superoxide dismutase-1 (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 70 publications
(123 reference statements)
0
28
0
Order By: Relevance
“…The biological heterogeneity of astrocytes in the healthy nervous system is, perhaps not surprisingly, correlated with the demonstration that not all astrocytes are equally susceptible to dysfunction in ALS, as well as other neurological conditions (Goursaud et al, 2009;Li et al, 2016;Bugiani et al, 2018;Köhler et al, 2021;Nguyen et al, 2021). Moreover, different types of astrocytes interact selectively with different motor neurons under both physiological and pathological conditions (Kelley et al, 2018a;Gomes et al, 2020;Mishra et al, 2020;Barbosa et al, 2021). More specifically, studies by Kelley and colleagues showed that loss of the inward-rectifying K + channel Kir4.1 in astrocytes located in the ventral horn of the murine spinal cord selectively alters large fast alpha-motor neuron size and function, leading to reduced peak strength (Kelley et al, 2018b).…”
Section: Astrocyte Heterogeneitymentioning
confidence: 76%
See 1 more Smart Citation
“…The biological heterogeneity of astrocytes in the healthy nervous system is, perhaps not surprisingly, correlated with the demonstration that not all astrocytes are equally susceptible to dysfunction in ALS, as well as other neurological conditions (Goursaud et al, 2009;Li et al, 2016;Bugiani et al, 2018;Köhler et al, 2021;Nguyen et al, 2021). Moreover, different types of astrocytes interact selectively with different motor neurons under both physiological and pathological conditions (Kelley et al, 2018a;Gomes et al, 2020;Mishra et al, 2020;Barbosa et al, 2021). More specifically, studies by Kelley and colleagues showed that loss of the inward-rectifying K + channel Kir4.1 in astrocytes located in the ventral horn of the murine spinal cord selectively alters large fast alpha-motor neuron size and function, leading to reduced peak strength (Kelley et al, 2018b).…”
Section: Astrocyte Heterogeneitymentioning
confidence: 76%
“…As discussed above, the regional and functional diversity of astrocytes in both the brain and spinal cord underlies specialized interactions of specific astrocyte populations with particular neuronal neighbors (Hochstim et al, 2008;Tsai et al, 2012;Bayraktar et al, 2014;Molofsky et al, 2014;Kelley et al, 2018a;Mishra et al, 2020), underscoring the importance of accounting for astrocyte heterogeneity when studying the involvement of astrocytes in neurodegenerative diseases such as ALS. Up to date, hiPSC-derived astrocyte cultures used to model ALS pathophysiology have usually included a mix of multiple types of astrocytes (e.g., Hall et al, 2017;Madill et al, 2017;Qian et al, 2017;Tyzack et al, 2017;Kelley et al, 2018a;Birger et al, 2019;Varcianna et al, 2019;Rajpurohit et al, 2020;Smethurst et al, 2020;Zhao et al, 2020).…”
Section: Taking Cellular Heterogeneity Into Consideration When Deriving Astrocytes From Human Induced Pluripotent Stem Cells For Als Modementioning
confidence: 99%
“…Compared to the published studies mainly conducted in ALS1 neural cells (e.g., motor neurons, astrocytes [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]) we chose primary fibroblasts (rFFFs) and bone marrow- mesenchymal stem cells (rBM-MSCs) from the ALS1 rat G93A as cell models. We demonstrated that the presence of the hallmarks of the disease broad in non-neural cells, and the signs increase with the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Non-cell autonomous toxicity to motoneurons has also been shown using conditioned media from human and mouse astrocytes expressing ALS-linked mutations ( SOD1 , TARDBP, C9ORF72 ) or that lack identified causes of ALS (sALS) [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ]. Despite considerable efforts, so far, the toxic factor released by ALS astrocytes has not been identified, although a recent study by the Przedborski laboratory indicates that mutant SOD1 astrocytes release a soluble protein(s) or fragment(s) between 5 and 30 kDa [ 143 ]. These and other studies rule out several usual suspect molecules, such as glutamate, ATP, oxygen and nitrogen reactive species, TNFα, and SOD1 [ 134 , 137 , 143 ].…”
Section: Contribution Of Mast Cells Hemichannels On Neuroinflammatmentioning
confidence: 99%
“…Despite considerable efforts, so far, the toxic factor released by ALS astrocytes has not been identified, although a recent study by the Przedborski laboratory indicates that mutant SOD1 astrocytes release a soluble protein(s) or fragment(s) between 5 and 30 kDa [ 143 ]. These and other studies rule out several usual suspect molecules, such as glutamate, ATP, oxygen and nitrogen reactive species, TNFα, and SOD1 [ 134 , 137 , 143 ]. Nonetheless, astrocytes release numerous additional small pro-inflammatory molecules or bioactive substances, which can have pathological effects on motoneurons (see Figure 2 ; [ 144 , 145 ]).…”
Section: Contribution Of Mast Cells Hemichannels On Neuroinflammatmentioning
confidence: 99%